Role of Product Quality, Need for Variety, Customer Satisfaction, and Switching Cost on Switching Behavior on Male Skincare Product - segoro, suluk waseso; Haryanto, Yudie; pramana, gilang widya; Hendriana, Evelyn (Accounting Department,, 2024)
Purpose — This study examines and analyses the influence of product quality, need for variety, customer satisfaction, and switching costs on customer switching intention in the men's skincare industry. Design/methodology/approach—Descriptive associative research was utilized to test the hypotheses. Data were collected via an online survey, where samples were chosen using a purposive technique involving male skin care and grooming product customers in various major cities in Indonesia. A valid 418 responses were analyzed using PLS-SEM. Findings — This study validated the significant effect of the need for variety, product quality, and customer satisfaction on customers switching intention. However, switching costs failed to moderate the relationship between customer satisfaction and switching intention. Practical implications—Producers of men’s skincare products must satisfy their target customers by offering more product variety, ensuring their products meet customers’ requirements, and maintaining their product quality. They must also keep innovating to produce new products, as customers tend to switch to other brands offering a new variety of products. Originality/value — It is one of a few studies focusing on the purchasing behaviour of men, particularly in emerging economies, despite the growing concerns of men about their appearance. Paper type — Research Paper